MODIFIED CRYPTOTIA RECONSTRUCTION USING LARGE Z-PLASTY AND CARTILAGE STRUT: A CASE REPORT - Rianto Noviady Ramli; Estelita Liana; Zulfa Tsurayya (Jurnal Rekonstruksi dan Estetik, 2026)
Highlights: A combined large Z-plasty and cartilage strut technique effectively corrects Type I cryptotia Simultaneous correction of skin deficiency and cartilage deformity improves surgical outcomes Intentional overcorrection of the cephaloauricular angle helps maintain long-term ear projection The technique provides adequate posterior auricular skin coverage and restores the auriculotemporal sulcus Favorable short-term results were achieved with no complications or recurrence Abstract Introduction: Cryptotia is a congenital auricular deformity characterized by burial of the upper portion of the ear beneath the temporal skin. Successful correction requires correction of both skin deficiency and cartilage deformity. Case Illustration: We report a case of Type I cryptotia treated with a combination of a large Z-plasty for posterior skin release and a conchal cartilage strut graft to widen the cephaloauricular angle. Intentional overcorrection was performed to ensure stable projection after skin closure. Discussion: The procedure provided adequate skin coverage, restored the cephaloauricular sulcus, and achieved a postoperative cephaloauricular angle of approximately 30 degrees, comparable to that of the contralateral normal ear. No complications or recurrence were observed during the one-month follow-up. Conclusion: This combined technique offers a promising approach for the correction of Type I cryptotia by simultaneously addressing both skin and cartilage abnormalities. Further studies with larger samples sizes and longer follow-up periods are needed to evaluate.